Ethics and the New Genetics : An Integrated Approach - Monsour, H. Daniel, 1958- (Book collections on Project MUSE., 2007)
Everyday, new advances are being made in the science of human genetics. Accompanying progress in this area, however, are new ethical dilemmas. At a think tank sponsored by the Canadian Catholic Bioethics Institute, an interdisciplinary group of ethicists, geneticists, physicians, lawyers, and theologians gathered in an attempt to apply some features of Bernard Lonergan's notion of functional specialization to ethical debates surrounding genetics.Editor H. Daniel Monsour has brought together a series of articles presented at this think tank. The articles accomplish two tasks: first, they explore some of the advances in human genetic that continue to prompt ethical debate and outline the different stances on those issues; second, they examine those stances in the context of Roman Catholic moral and religious thought. Timely, innovative, and wide-ranging, this collection will be of interest to bioethicists and philosophers, as well as religious and Lonerganian scholars.